The potential for minimally invasive intracerebral hemorrhage evacuation in routine healthcare: applicability of the ENRICH trial criteria to an unselected cohort - Apostolaki-Hansson, Trine; Hillal, Amir; Göransson, Nathanael; Hansen, Björn M.; Norrving, Bo; Ramgren, Birgitta; Wassélius, Johan; Ullberg, Teresa (Frontiers in Stroke, 2024)
Objective Following the favorable outcomes demonstrated by the Early MiNimally-invasive Removal of IntraCerebral Hemorrhage (ENRICH) trial in supratentorial intracerebral hemorrhage (ICH) patients treated with minimally invasive surgery (MIS), and considering the increasing interest in MIS, we aimed to assess the potential eligibility rate for ICH patients in Sweden. Methods All patients with spontaneous ICH in the Swedish Stroke Register (RS) during 2017–2020 in Skane county (1.37million) were assessed. Baseline imaging was used for radiological characterization. Clinical data were obtained from RS. MIS eligibility in the total ICH population meeting ENRICH criteria were estimated and extrapolated to the Swedish population (10.5million). Results Of 1314 ICH patients, 5.9% met the ENRICH criteria for MIS (ICH volume 30–80ml). Considering the ENRICH trial results indicating the effectiveness of MIS was mainly attributable to intervention for lobar hemorrhages, we determined that 2.8% of our ICH cohort in Sweden would be eligible for MIS. The estimated rate of neurosurgery for ICH could increase from the current 1.46 to 1.90 patients/100000 population/year (in absolute numbers from 154 to 200 interventions out of 2400 ICHs in Sweden annually). Conclusions We show that 2.8% of the Skane ICH population would be eligible for MIS if ENRICH criteria are employed for patients with lobar ICH, corresponding to a 29% increase of current surgical rates for ICH in Sweden. As MIS for ICH is not yet standard practice in Sweden, consideration for its implementation within the neurosurgical organization becomes essential to accommodate the anticipated increase in patient demand.